BUILDING DIGITAL POTENTIAL IN MANAGING GOVERNMENT ORGANIZATION IN RESPONSE TO TECHNOLOGICAL CHANGE - Promchana, Chestapat; Chandarasorn, Voradej; Chirinang, Pensri; Mankan, Whiphat (Journal of MCU Nakhondhat, 2024)
This article will discuss ideas for building digital potential in government organization management in the era of using digital technology in organizational management. In order to strengthen standards and raise the level of work of government organizations to be more efficient. In the context of a world that is fully transitioning to the digital era. Which at present, with the structure of government organizations being large and complex compliance with rules or regulations that support the operations of government organizations in transforming into digital organizations. The management of public sector organizations is strict and has rules and regulations. Management without the ability to use technology to effectively manage government organizations. This makes the management of government organizations in many sectors complicated in management and causes various problems. Building digital potential in government organizations is therefore one of the important success factors for increasing efficiency and effectiveness in managing government organizations in this era. In order to lead to further development and support for changes occurring in the digital environment for government organizations. Therefore, in digital organization management for government organizations to be successful. There must be real development in building digital potential in government organizations which must be developed simultaneously in three dimensions, namely 1) development and deployment of digital technology 2) development of digital procedures and 3) development of personnel. To serve as a guideline for preparation of government organizations towards entering the digital era which increases efficiency and effectiveness in managing government organizations to drive government organizations towards digital sustainability.